Study Content Character in Social Studies Learning (A study in Public Junior High School at Batang District, Central Java) - Fitria, Putri Nur; Juhadi, Juhadi; Subagyo, Subagyo (JESS (Journal of Educational Social Studies), 2018)
The implementation of character education in the formal environment is effective in respond to it the moral crisis, and other social problems. The purpose of this study is to examine the implementation of independent character education and integrity in social studies learning. The approach used in this study is qualitative and quantitative approaches. Research data was obtained from school principals, teachers and students. Data collection techniques using observation, interviews, and documentation studies. Data analysis techniques in this study were carried out with qualitative descriptions. By reviewing the rational relationships experienced by the subject without making up, by analyzing the character of each student in social studies learning. The sampling technique was purposive sampling to select participants based on the ability of informants to provide answers related to the experience studied in accordance with the implementation of characters in social studies learning. The findings show that religious and nationalist characters are new findings in planning learning in Public Junior High Schools in Batang District. However, overall the application of character content is not optimal. It can be seen from the inclusion of the focus of the characters in RPP that it has not been explicitly distributed to students, on the other hand, independent character and integrity can directly grow the modeling process that is imitated during the learning process. This study concluded that social cognitive theory with the modeling process has a good impact on the character of a student because it can foster examples of good characters for other students.